The Protective Effects of IL-31RA Deficiency During Bleomycin-Induced Pulmonary Fibrosis - Yombo, Dan J. K.; Odayar, Varshini; Gupta, Nishant; Jegga, Anil G.; Madala, Satish K. (Frontiers in Immunology, 2021)
Idiopathic Pulmonary Fibrosis (IPF) is a severe fibrotic lung disease characterized by excessive collagen deposition and progressive decline in lung function. Th2 T cell-derived cytokines including IL-4 and IL-13 have been shown to contribute to inflammation and fibrotic remodeling in multiple tissues. Interleukin-31 (IL-31) is a newly identified cytokine that is predominantly produced by CD4 Th2 T cells, but its signaling receptor IL-31RA is primarily expressed by non-hematopoietic cells. However, the potential role of the IL-31-IL31RA axis in pulmonary inflammation and fibrosis has remained largely unknown. To determine the role of IL-31RA deficiency in pulmonary fibrosis, wildtype, and IL-31RA knockout mice were treated with bleomycin and measured changes in collagen deposition and lung function. Notably, the loss of IL-31 signaling attenuated collagen deposition and lung function decline during bleomycin-induced pulmonary fibrosis. The total lung transcriptome analysis showed a significant reduction in fibrosis-associated gene transcripts including extracellular matrix and epithelial cell-associated gene networks. Furthermore, the lungs of human IPF showed an elevated expression of IL-31 when compared to healthy subjects. In support, the percentage of IL-31 producing CD4+ T cells was greater in the lungs and PBMCs from IPF patients compared to healthy controls. Our findings suggest a pathogenic role for IL-31/IL-31RA signaling during bleomycin-induced pulmonary fibrosis. Thus, therapeutic targeting the IL-31-IL-31RA axis may prevent collagen deposition, improve lung function, and have therapeutic potential in pulmonary fibrosis.